The anticonvulsant and behavioural profile of L-687,414, a partial agonist acting at the glycine modulatory site on the N-methyl-D-aspartate (NMDA) receptor complex. - Tricklebank, M D (1994)
1. The anticonvulsant and behavioural effects of the glycine/NMDA receptor partial agonist, L-687,414 (R(+)-cis-beta-methyl-3-amino-1-hydroxypyrrolid-2-one) have been investigated in rodents. 2. L-687,414 dose-dependently antagonized seizures induced by N-methyl-D,L- aspartic acid (NMDLA, ED50 = 19.7 mg kg-1), pentylenetetrazol (PTZ, ED50 = 13.0 mg kg-1) and electroshock (ED50 = 26.1 mg kg-1) when given intravenously 15 min before test, in male Swiss Webster mice but was most potent against audiogenic seizures induced by a 120 dB bell in DBA/2 mice (ED50 = 5.1 mg kg-1, i.p., 30 min before test). 3. L-687,414 also induced impairments of performance in a rotarod test in both Swiss Webster and DBA/2 mice and the ratio [rotarod MED:anticonvulsant ED50] varied between 0.9 and 5, depending on the convulsant used. 4. Similar behaviours to those seen after administration of the non-competitive NMDA receptor antagonist, MK-801 (head weaving, body rolling, hyperlocomotion) were seen in the mouse after giving L-687,414, although the peak effect occurred at a dose (100 mg kg-1) which was 5-20 times the anticonvulsant ED50S, depending on the convulsant used. Unlike MK-801, however, doses of L-687,414 that were behaviourally stimulant did not increase dopamine turnover in the nucleus accumbens. 5. Consistent with the interaction of L-687,414 with the glycine/NMDA receptor, the anticonvulsant, ataxic and motor stimulant effects of the compound were significantly attenuated by the glycine/NMDA receptor agonist, D-serine (10-100 micrograms per mouse, i.c.v.).(ABSTRACT TRUNCATED AT 250 WORDS)